Validation of the Maslach Burnout Inventory-General Survey 9-item short version: psychometric properties and measurement invariance across age, gender, and continent - Wang, Anni; Duan, Yinfei; Norton, Peter G.; Leiter, Michael P.; Estabrooks, Carole A. (Frontiers in Psychology, 2024)
Background: The Maslach Burnout Inventory-General Survey (MBI-GS) stands as the preeminent tool for assessing burnout across various professions. Although the MBI-GS9 emerged as a derivative of the MBI-GS and has seen extensive use over several years, a comprehensive examination of its psychometric properties has yet to be undertaken.: This study followed the Standards for Educational and Psychological Testing guidelines to validate the MBI-GS9. Employing a combined approach of classical test theory and item response theory, particularly Rasch analysis, within an integrated framework, the study analyzed data from 16,132 participants gathered between 2005 and 2015 by the Centre for Organizational Research at Acadia University.Results: Findings revealed that the MBI-GS9 exhibited satisfactory reliability and validity akin to its predecessor, the MBI-GS. Across its three dimensions, Cronbach's α and Omega coefficients ranged from 0.84 to 0.91. Notably, the MBI-GS9 displayed no floor/ceiling effects, demonstrated good item fit, ordered threshold, acceptable person and item separation and reliability, clear item difficulty hierarchy, and a well-distributed item threshold. However, results suggested a recommended minimum sample size of 350 to mitigate potential information loss when employing the MBI-GS9. Beyond this threshold, the observed mean difference between the MBI-GS and MBI-GS9 held minimal practical significance. Furthermore, measurement equivalence tests indicated that the MBI-GS9 maintained an equivalent three-factor structure and factor loadings across various gender, age, and continent groups, albeit with inequivalent latent values across continents.In sum, the MBI-GS9 emerges as a reliable and valid alternative to the MBI-GS, particularly when utilized within large, diverse samples across different age and gender demographics. However, to address potential information loss, a substantial sample size is recommended when employing the MBI-GS9. Additionally, for cross-cultural comparisons, it is imperative to initially assess equivalence across different language versions at both the item and scale levels.